Dramatic transformations: Integrating theatre in English language teacher education - Putri, Diannike; Kristanto, Barlian; Sukmawati, Ida Dian (Yayasan Mitra Persada Nusantara, 2025)
The integration of drama in English language teacher education offers transformative potential that has not been fully explored. In an increasingly complex era of globalization, English language teacher education faces the challenge of preparing educators who are not only linguistically proficient but also capable of adapting to diverse cultural and pedagogical contexts. This study aims to analyze the impact of a dramaturgical approach on the development of linguistic competence, professional identity, and pedagogical creativity of prospective English language teachers. Using a longitudinal case study design with a mixed-methods approach, this research involved two pre-service teachers over one academic semester. Data were collected through assessment rubrics for drama scripts and videos, in-depth interviews, and participant observation, with analysis employing both descriptive statistics and thematic analysis techniques. Results revealed significant improvements in linguistic and performative skills, with scores increasing from script writing to video production (15 to 18 and 13 to 20). Qualitative analysis identified five key phenomena: Multimodal Linguistic Neuroplasticity, Professional Identity Reconfiguration through Performativity, Deconstruction of Language Skills Hierarchy, Theatre as a Sociolinguistic Reality Simulator, and Pedagogical Liminality. These findings collectively establish the foundation for a